Unraveling trajectories from aplastic anemia to hematologic malignancies: genetic and molecular insights - Kim, Namsoo; Choi, Yu Jeong; Lee, Seung-Tae; Choi, Jong Rak; Lyu, Chuhl Joo; Shin, Saeam; Cheong, June-Won (Frontiers in Oncology, 2024)
Background Aplastic anemia (AA), characterized by hematopoietic stem cell deficiency, can evolve into different hematologic malignancies. Our understanding of the genetic basis and mechanisms of this progression remains limited. Methods We retrospectively studied 9 acquired AA patients who later developed hematologic malignancies. Data encompassed clinical, laboratory, karyotype, and next-generation sequencing (NGS) information. We explored chromosomal alterations and mutation profiles to uncover genetic changes underlying the transition. Results Nine AA patients developed myelodysplastic syndrome (seven patients), acute myeloid leukemia (one patient), or chronic myelomonocytic leukemia (one patient). Among eight patients with karyotype results at secondary malignancy diagnosis, monosomy 7 was detected in three. Trisomy 1, der(1;7), del(6q), trisomy 8, and del(12p) were detected in one patient each. Among three patients with NGS results at secondary malignancy diagnosis, KMT2C mutation was detected in two patients. Acquisition of a PTPN11 mutation was observed in one patient who underwent follow-up NGS testing during progression from chronic myelomonocytic leukemia to acute myeloid leukemia. Conclusion This study highlights the genetic dynamics in the progression from AA to hematologic malignancy. Monosomy 7’s prevalence and the occurrence of PTPN11 mutations suggest predictive and prognostic significance. Clonal evolution underscores the complexity of disease progression.